American hustle [videorecording (Blu-Ray + DVD)] - Russell, David O., 1958-; Singer, Eric Warren; Sandgren, Linus; Elfman, Danny; Bale, Christian, 1974-; Cooper, Bradley; Adams, Amy; Renner, Jeremy; Lawrence, Jennifer, 1990-; C. K., Louis; Peña, Michael, 1976-; Nivola, Alessandro (2014)
Brilliant con man Irving Rosenfeld, along with his equally cunning and seductive British partner Sydney Prosser, is forced to work for wild FBI agent Richie DiMaso. DiMaso pushes them into a world of Jersey powerbrokers and mafia that's as dangerous as it is enchanting. Carmine Polito is the passionate, volatile, New Jersey political operator caught between the cons and Feds. Irving's unpredictable wife Rosalyn could be the one to pull the thread that brings the entire world crashing down.